2017
DOI: 10.1080/14683849.2017.1392860
|View full text |Cite|
|
Sign up to set email alerts
|

Ethnic conflict and gender inequality in education: the case of Turkey

Abstract: Although conflict remains a major obstacle to development in many areas of the world, its impact on education has been rarely studied. This article investigates the relationship between conflict and gender equality, focusing on the schooling of the girls in the conflict-ridden regions of Turkey. Patriarchy is the most important determinant of low educational levels among girls in Southeastern Turkey. However, ethnic conflict exacerbates male-dominant traditions and blocks economic development, reinforcing patr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Moreover, a number of recent studies find that girls are also subjected to increased levels of GBV from their own communities during and after armed conflict (Read-Hamilton and Marsh 2016;Verwimp and Van Bavel 2013). Sommer et al find that high incidences of violence and its consequent normalisation in society lead to men and boys to assert a more harmful, violent form of masculinity (Sommer et al 2018a(Sommer et al , 2018bKılınç et al 2018). Other studies found conflict to be associated with increased levels of intimate partner violence (IPV) (Østby 2016;Anderlini 2011).…”
Section: A211 Physical Security and Gender-based Violence (Gbv)mentioning
confidence: 99%
“…Moreover, a number of recent studies find that girls are also subjected to increased levels of GBV from their own communities during and after armed conflict (Read-Hamilton and Marsh 2016;Verwimp and Van Bavel 2013). Sommer et al find that high incidences of violence and its consequent normalisation in society lead to men and boys to assert a more harmful, violent form of masculinity (Sommer et al 2018a(Sommer et al , 2018bKılınç et al 2018). Other studies found conflict to be associated with increased levels of intimate partner violence (IPV) (Østby 2016;Anderlini 2011).…”
Section: A211 Physical Security and Gender-based Violence (Gbv)mentioning
confidence: 99%
“…Moreover, a number of recent studies find that girls are also subjected to increased levels of GBV from their own communities during and after armed conflict (Read-Hamilton and Marsh 2016;Verwimp and Van Bavel 2013). Sommer et al find that high incidences of violence and its consequent normalisation in society lead to men and boys to assert a more harmful, violent form of masculinity (Sommer et al 2018a(Sommer et al , 2018bKılınç et al 2018). Other studies found conflict to be associated with increased levels of intimate partner violence (IPV) (Østby 2016;Anderlini 2011).…”
Section: A211 Physical Security and Gender-based Violence (Gbv)mentioning
confidence: 99%